Exploring Time-Dependent Concerns about Pregnancy and Childbirth from Search Logs - Fourney, Adam; White, Ryen W.; Horvitz, Eric (Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems (CHI '15), 2015)
We study time-dependent patterns of information seeking about pregnancy, birth, and the first several weeks of caring for newborns via analyses of queries drawn from anonymized search engine logs. We show how we can detect and align web search behavior for a population of searchers with the natural clock of gestational physiology via proxies for ground truth based on searchers' self-report queries (e.g., [I am 30 weeks pregnant and my baby is moving a lot]). Then, we present a methodology for performing additional alignments, that are valuable for learning about the concerns, curiosities, and needs that arise over time with pregnancy and early parenting. Our findings have implications for learning about the temporal dynamics of pregnancy-related interests and concerns, and also for the design of systems that tailor their responses to point estimates of each searcher's current stage in pregnancy.h
Best of CHI honorable mention